Tanggapan Siswa Terhadap Pembelajaran Jarak Jauh Mata Pelajaran Pendidikan Agama Katolik dan Budi Pekerti di SMP Katolik Pato Nonongan - Hilda Natalia; Carolus Patampang; Hendrik Palimbo (Dinasti Research, 2021)
This study aims to determine students' responses to distance learning in the subjects of Catholic Religious Education and Moral Education at Pato Nonongan Catholic Middle School. The author uses qualitative research methods with interview and documentation techniques. The six informants in this study came from students of class VII and VIII at Pato Nonongan Catholic Middle School. This study reveals that distance learning seems new to students because they are not used to following it. As a result, they feel confused, strange, and unhappy, especially when they have to find new learning tools. For their commitment, they can feel the positive impact of distance learning. Students also learn valuable lessons, including discipline and respect for time. The results of this study can be used as input for teachers and policymakers to take steps to develop better distance learning.